Support and information needs of parents and carers of preterm babies requiring respiratory support on the neonatal unit: A qualitative systematic review. Issue 2 (April 2020) - Tan, Audrey; Pelone, Ferruccio; Arnold, Stephanie; Anderson, Josie; Kennedy, Gillian; Goodman, Joanna
Abstract: Preterm babies who require respiratory support are often connected to invasive ventilation equipment or oxygen administration equipment. The practical difficulties that families might face in being with, and caring for, their baby can cause additional anxiety and upset. Nine databases were systematically searched from 1990 to 2019. Primary qualitative studies from OECD countries with a substantial focus on support and information needs of parents and carers of preterm babies requiring respiratory support on the Neonatal Intensive Care Unit (NICU) were included. A meta-synthesis was used to analyse included evidence. Six themes were identified from 18 inluded studies: social and psychological support, staff support, parent-to-parent support, hospital environment, employment support and information formats. This review of qualitative studies identified potential benefits of implementing support valued by parents or carers of preterm babies receiving respiratory care.